Evaluasi Batas Konsentrasi Parameter Indeks Standar Pencemar Udara (ISPU) pada Kawasan Industri di Pulau Jawa - Alusvigayana, Pryanka; Yuwono, Arief Sabdo; Yani, Mohamad; Syarwan, Supandi (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2023)
Due to the harmful effects of air pollution on health, outdoor air pollution standards are getting stricter. Because of environmental changes, the Minister of Environment and Forestry Regulation No. 14/2020 must reevaluate the concentration limits for ISPU parameters. This study aimed to examine the concentration ranges and ISPU values for SO2, NO2, CO, O3, and PM10 in industrial estates on Java Island, and set concentration limits for five relevant ISPU parameters based on the results of monitoring, sampling, and toxicity studies. A drop in the average concentration of the five ISPU parameters in 2022 compared to monitoring from 2015 to 2019 shows that the air quality in industrial estates on Java Island is improving. The ISPU values between 10 and 56 are in the good-to-moderate range, which means that the air quality is still good enough for the health of humans, animals, and plants. The relevant concentration limit recommendations for ISPU in good-to-moderate categories for SO2, NO2, CO, O3, and PM10 were 42–77 μg/Nm3, 29–120 μg/Nm3, 3519–5037 μg/Nm3, 33–97 μg/Nm3, and 29–82 μg/Nm3, respectively. The results of this study can be used to improve Indonesia’s ambient air quality index system (ISPU).